Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada PT. Sumber Alfaria Trijaya Tbk. - Riska Jangko; Raflin Hinelo; Abdulrahim Maruwae; Meyko Panigoro; Melizubaida Mahmud; Maya Novrita Dama (State University of Gorontalo, 2023)
It employed a quantitative approach with a survey research method. The data used were primary data obtained from distributing questionnaires to customer at PT. Sumber Alfaria Trijaya Tbk, Dumoga Timur Subdistrict, Bolaang Mongondow Regency, with a total sample of 32 respondents. The research finding depicted that service quality had a positive and significant effect on costumer satisfaction, which meant that the better the service quality provided by PT Sumber Alfaria Trijaya Tbk, Dumoga Timur Subdistrict, Bolaang Mongondow Regency, the better the costumer satisfaction who shop at the company. The coefficient of determination research was equal to 74.3% which meant that the variability of customer satisfaction could be explained by the service quality of 74,3%.